Cloud-Enabled Interactive Sound Propagation for Untethered Mixed Reality - Chemistruck, Mike; Storck, Kyle; Raghuvanshi, Nikunj (AES International Conference on Audio for Virtual and Augmented Reality (AVAR), 2020)
We describe the first system for physically-based wave acoustics including diffraction effects within a holographic experience shared by multiple untethered devices. Our system scales across standalone mobile-class devices, from a HoloLens to a modern smart phone. Audio propagation in real-world scenes exhibits perceptually salient effects that complement visuals. These include diffraction losses from obstruction, re-direction (“portaling”) of sounds around physical doorways and corners, and reverberation in complex geometries with multiple connected spaces. Such effects are necessary in mixed reality to achieve a sense of presence for virtual people and things within the real world, but have so far been computationally infeasible on mobile devices. We propose a novel cloud-enabled system that enables such immersive audio-visual scenarios on untethered mixed reality devices for the first time. Talk and Demo can be viewed here